Роль інноваційних технологій для формування у майбутніх психологів професійної компетентності - Орос Ільдіко; Orosz Ildikó; Oros Ildiko; Бергхауер-Олас Емйовке; Berghauer-Olasz Emőke; Кучай Тетяна; Kuchai Tatiana; Kucsáj Tetjána (Видавництво «Код», 2025)
Резюме. У статті з’ясовано найсуттєвіші шляхи формування професійної компетентності у майбутніх психологів засобами інноваційних технологій. Розкрито технології змішаного навчання, що є головним способом стимулювання ініціативної, гнучкої і відповідальної практики формування професійної компетентності у майбутніх психологів.

Abstract. Today, it is important to introduce innovative strategies and technologies into the professional training of future psychologists, to improve and form professional competence, in order to be able to provide, in the conditions of the new educational reality, effective not only theoretical, but also practical training of psychologists for professional activity. The article clarifies the most significant ways of forming professional competence in future psychologists by means of innovative technologies. Among the popular innovative technologies in the educational process for forming professional competence in future psychologists, there are psychocorrection technologies, in particular training technologies. Group psychocorrection is aimed at the destruction of the psyche, requires an understanding of its features. Blended learning technologies are disclosed, which are the main way to stimulate proactive, flexible and responsible practice of forming professional competence in future psychologists. Project technology for forming professional competence in future psychologists allows to better realize the importance of acquired skills and knowledge acquired by them due to the possibility of their application in the practical sphere. Information and communication technologies significantly expand the possibilities of transmitting information and receiving it, contribute to the effective development of rhetorical skills and abilities, and the assimilation of rhetorical knowledge. Multimedia properties are the basis of ICT. Distance learning deserves special attention in the modern system of forming professional competence in future psychologists (learning in a virtual learning environment). In connection with the trends in the development of web technologies, the introduction of blogs, web quests, electronic educational and methodological complexes, personal web pages significantly expands the use of active methods, the possibilities of resource support for independent work. Inclusive learning technologies deserve attention in the formation of professional competence in future psychologists, as they contribute to the adaptation of student identity, determine the implementation of online platforms for continuing education in higher education institutions.
The role of innovative technologies in forming professional competence in future psychologists
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00015728 Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-11
Keywords: інноваційні технології; майбутні психологи; професійна компетентність; заклади вищої освіти; конкурентоздатність фахівців